Peran Uptd Perlindungan Perempuan Dan Anak Dalam Penanganan Tindak Kekerasan Anak Di Kota Surakarta - Maya Desvira Riandy; Rifayani Hastuti (Pusat Riset dan Inovasi Nasional, 2024)
Surakarta is a metropolitan city, of course the ease of access to report cases of child violence is also higher. With its big city status, it does not rule out the possibility that the problem of violence against children continues to exist in Surakarta. The problem of violence against children experiences a cycle of ups and downs in each region. In Surakarta itself, cases of violence against children have increased in the last three years. This is of course a concern for the Surakarta City government. The role of the Government, especially the Surakarta City PPA UPTD, has been good in protecting, preventing and handling cases of child violence. This research aims to describe and analyze the role of the regional technical implementation unit for the protection of women and children (UPTD PPA) in assisting victims of violence against children in the city of Surakarta. In addition, this research aims to describe the obstacles faced by UPTD PPA in assisting victims of violence against women in the city of Surakarta. This study used descriptive qualitative method. Researchers collect data, observations, interviews and documentation to obtain complete and detailed data. The subjects of this research were: (1) Head of Department, (2) Head of UPTD PPA, (3) Head of Child Protection, (4) Legal counselor, (5) Psychological counselor, and (6) 2 clients. Data analysis was carried out using inductive data analysis techniques. Checking the validity of the data uses triangulation techniques. The results of this research are (1) the role of UPTD PPA in assisting victims of violence against children, namely: a) role in dealing with children who are victims of violence, b) assisting in the health recovery of children who are victims of violence, c) psychological assistance to children who are victims of violence, d) legal assistance to children who are victims violence, e) role in psychoeducation in the environment of children who are victims of violence (2) obstacles faced by UPTD PPA, namely the lack of human resources in UPTD PPA Surakarta City, namely psychological counselors and victims of violence who do not want to report cases of violence they experience.